Gaya Kepemimpinan Transformasional terhadap Kebijakan Publik: Systematic Literature Review Kasus Kepemimpinan Susi Pudjiastuti - Hani Humaeriyah; Devia Izmi Nurshanti; Layalia Auliaur Rahman; Rd. Ghina Fithriyah; Risnawati Aisy (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze transformational leadership styles in the context of public policy thru a literature review of Susi Pudjiastuti's leadership. The research uses a qualitative approach with the Systematic Literature Review (SLR) method on various literature sources discussing transformational leadership, public leadership, and public policy. The study results indicate that transformational leadership plays a crucial role in driving bureaucratic reform, improving the quality of public services, and strengthening innovation and organizational capabilities in the public sector. In the case study, Susi Pudjiastuti's leadership represents transformational leadership practices thru policy assertiveness, a vision of maritime sovereignty, and the courage to confront resistance in public policy formation, such as eradicating illegal fishing. Although the resulting policies have a significant impact, transformational leadership also faces challenges in the form of public pros and cons, necessitating effective policy.